Suppression of multiple power line harmonic interference for low frequency signals - Trudeau, L C; Gagnon, F (Electronics letters, 2013)
In this paper, a novel and simple algorithm capable of extracting and cancelling harmonic disturbance from signals subject to severe power line interference is presented. The key element consists of the adaptation of a filter to a deterministic harmonic reference closely correlated to the interference. The resulting signal is optimal in the mean squared error sense. Simulation results show that this carefully crafted adaptive scheme can improve by up to 30 dB the signal to interference ratio. Minimal remaining interference and fast convergence are obtained by optimisation of the algorithm's parameters.